KARAKTERISTIK TANAH LEMPUNG LAPUKAN FORMASI BALIKPAPAN DI SAMBOJA, KALIMANTAN TIMUR - Zakaria, Zufialdi -; Dipatunggoro, Geni -; Haryanto, Edi Tri - (Bulletin of Scientific Contribution, 2007)
Balikpapan Formation (Upper Middle Miosen) consist of quarzite sandstone, silty claystone, and shale with marl as intercalation, limestone and coal. clay at Samboja as apart of Balikpapan Formation, consist of silt, clay and sand.Clay identification based on soil mechanic is clay with high plasticity (CH), illitic, very low permeability (K = 6,61E-08 to 1,48E-07 cm/sec), medium to medium-high activity (A= 0.55 to 0.91)Keywords: clay, soil mechanic